Animação em motion graphics para a prevenção do bullying em escolas brasileiras - Amaral, Elidiany Andreia de Oliveira do (2019)
This research has data of the project entitled "Animation in motion graphics for the prevention of bullying in Brazilian schools.", With the purpose of bringing knowledge and alert parents and teachers about this problem that mainly affects children and adolescents, assisting in the fight and in the prevention of such violent acts. Using animation as a means of communication, with the intention of arousing the curiosity and interest of the viewer in a light and easy to understand. Will be done in this research studies on the subject, script development, storyboard, soundtrack, narration and animation.